3-Dimensional printing guide template assisted percutaneous vertebroplasty: Technical note. (June 2018) - Li, Jian; Lin, JiSheng; Yang, Yong; Xu, JunChuan; Fei, Qi
Highlights: Digital design provides comprehensive evaluation and individualized surgical plan. The good fitting of skin and template can make operation more stable and accurate. This technique may increase precision, decrease radiation exposure and surgical time. Abstract: Percutaneous vertebroplasty (PVP) is currently considered as an effective treatment for pain caused by acute osteoporotic vertebral compression fracture. Recently, puncture-related complications are increasingly reported. It's important to find a precise technique to reduce the puncture-related complications. We report a case and discussed the novel surgical technique with step-by-step operating procedures, to introduce the precise PVP assisted by a 3-dimensional printing guide template. Based on the preoperative CT scan and infrared scan data, a well-designed individual guide template could be established in a 3-dimensional reconstruction software and printed out by a 3-dimensional printer. In real operation, by matching the guide template to patient's back skin, cement needles' insertion orientation and depth were easily established. Only 14 times C-arm fluoroscopy with HDF mode (total exposure dose was 4.5 mSv) were required during the procedure. The operation took only 17 min. Cement distribution in the vertebral body was very good without any puncture-related complications. Pain was significantly relieved after surgery. In conclusion, the novel precise 3-dimensional printing guide template system may allow (1) comprehensive visualization of the fractured vertebral body and the individual surgical planning, (2) the perfect fitting between skin and guide template to ensure the puncture stability and accuracy, and (3) increased puncture precision and decreased puncture-related complications, surgical time and radiation exposure.